Dr. Jose Antonio Martínez Fernández — Deep Plane Facelift — Seville - Martínez Fernández, Jose Antonio (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Jose Antonio Martínez Fernández, practicing in Seville, Spain. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-002965; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; spain; seville